The Effect of Anthocyanins on Blood Pressure: A PRISMA-Compliant Meta-Analysis of Randomized Clinical Trials. Issue 15 (April 2016) - Zhu, Yongjian; Bo, Yacong; Wang, Xi; Lu, Wenjie; Wang, Xule; Han, Zhanying; Qiu, Chunguang
Abstract : Abstract: The findings of clinical studies concerning the association between anthocyanins supplementation and blood pressure (BP) are inconsistent. In order to provide a more precise estimate of the overall effect of anthocyanins on systolic blood pressure (SBP) and diastolic blood pressure (DBP), we conducted a meta-analysis of clinical trials about anthocyanins supplementation and BP. PubMed, Web of Science, Wanfang Database, and China National Knowledge Infrastructure (CNKI) (until October 2015) were searched to identify potential studies with information on anthocyanins extract supplementation and arterial BP. The weighted mean difference (WMD) and 95% confidence interval (CI) were used as a summary statistic. Net changes in SBP and DBP between anthocyanins supplementation and placebo groups were calculated by subtracting the values at end of follow-up from those at baseline. Meta regression was used to explore the potential moderators of effect size. The publication bias was assessed using Begger's Funnel plots and Egger's tests; P < 0.05 was considered to be statistically significant. Finally, 6 clinical studies with 472 participants for the effect of anthocyanins consumption on BP were included in the present meta-analysis. There is no significant effect on either SBP (WMD: 1.15 mm Hg, 95% CI: −3.17 to 5.47, I 2 = 56%) or DBP (WMD: 1.06 mm Hg, 95% CI: −0.71 to 2.83, I 2 = 0%) following supplementation with anthocyanins. In summary, results from this meta-analysis do not favor any clinical efficacy of supplementation with anthocyanins in improving blood pressure. Further well-designed large randomized controlled trials (RCTs) with long follow-up period are needed to verify the association of anthocyanins supplementation and blood pressure.